Arabic Language Teachers’ Readiness for Task-Based Language Teaching in the 21st Century: Insights from ACTFL Standards - Hasnil Oktavera; Abdul Hakim; Sutaman; Nurhadi; Abdurrahman Wahid Abdullah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
Task-Based Language Teaching (TBLT) is essential for developing 21st-century Arabic language skills. This study aims to assess the readiness of Indonesian Arabic language teachers to implement TBLT, utilizing the comprehensive ACTFL World-Readiness Standards (5Cs): communication, cultures, connections, comparisons, and communities, as the analytical framework. Employing a quantitative survey design, data were collected from Arabic teachers across various educational levels in Indonesia to evaluate their current preparedness levels against the 5Cs standard. The overall readiness index stands at 3.01 (on a 5-point scale), concluding that the teachers are “not ready, need some repairs” for full TBLT implementation. While Communication demonstrated the highest readiness (3.36), aspects like Comparisons (2.85) and Cultures (2.87) showed the lowest scores. These findings provide a crucial evaluation of teachers' preparedness, highlighting an urgent need for targeted professional development programs focused on integrating cultural competency and comparative linguistic skills within TBLT pedagogy to meet the demands of 21st-century language education.